Optimalisasi UMKM Melalui Edukasi Branding dan Inovasi Packaging di Desa Bandardawung - Dyah Yuni Kurniawati; Fairuz Rahmawati; Syifa Albalqis Danayomi; Intanita Nurlaili Rosyada; Dona Puan Maharani; Addina Harir Nur Azka; Sari Ayu Dwi Lestari; Rahmat Yanuar; Aldito Sadewo Putranto (BADAN PENERBIT STIEPARI PRESS, 2024)
Marketing strategies by optimizing branding and packaging are necessary because packaging not only functions as a storage container but can also attract more consumers. This community service aims to give awareness of the importance of product branding and introduce packaging innovations that can be implemented by business owners. This research method uses qualitative methods with observation and interviews as data collection techniques. The results showed that training on branding and packaging innovation succeeded in enhancing product packaging skills and increase understanding of the importance of branding in marketing products. In addition, improvements in branding and packaging are expected to increase product sales, empower the local economy, and improve the sustainability of SMEs in Bandardawung Village.